ASEAN-EU Partnership: Historical Development and Prospects in the Context of Indonesia's ASEAN Chairmanship in 2023 - Vătăman Dan* (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This year we mark 46 years of ASEAN-EU partnership, a period during which the two parties have endeavoured to expand and diversify their relationship. Considering that the ASEAN’s relationship with EU was elevated to a Strategic Partnership in December 2020, the purpose of this study is to highlight the most important milestones in bilateral relations and also to analyse how this cooperation has contributed to developed a dynamic and multifaceted partnership which covers political, security, economic, environmental, climate and socio-cultural issues. To achieve this proposed goal, qualitative and quantitative research methods were used, using written data, but also logical or statistical observations to draw conclusions. As well, inductive reasoning conducted the research from the specific of the ASEAN-EU partnership to the general situations, while deductive reasoning allowed to make an inference by going from general premises to specific and relevant conclusions. Taking into account the Indonesia's ASEAN Chairmanship in 2023, the study also aims to emphasize the 30th ASEAN-EU Joint Cooperation Committee Meeting convened in Jakarta, on which occasion the both sides reaffirmed their commitment to strengthening ASEAN-EU cooperation and to uphold ASEAN centrality based on shared relevant fundamental principles of their respective Indo-Pacific approaches.